Cardiac dysfunction and remodeling regulated by anti-angiogenic environment in patients with preeclampsia: the ANGIOCOR prospective cohort study protocol - Johana Ullmo; Monica Cruz-Lemini; Olga Sánchez-García; Lidia Bos-Real; Patricia Fernandez De La Llama; Francesca Calero; Carla Domínguez-Gallardo; Carmen Garrido-Gimenez; Cristina Trilla; Francesc Carreras-Costa; Alessandro Sionis; Josefina Mora; et al. (BMC, 2021)
Abstract Background Cardiovascular diseases (CVD) are cause of increased morbidity and mortality in spite of advances for diagnosis and treatment. Changes during pregnancy affect importantly the maternal CV system. Pregnant women that develop preeclampsia (PE) have higher risk (up to 4 times) of clinical CVD in the short- and long-term. Predominance of an anti-angiogenic environment during pregnancy is known as main cause of PE, but its relationship with CV complications is still under research. We hypothesize that angiogenic factors are associated to maternal cardiac dysfunction/remodeling and that these may be detected by new cardiac biomarkers and maternal echocardiography. Methods Prospective cohort study of pregnant women with high-risk of PE in first trimester screening, established diagnosis of PE during gestation, and healthy pregnant women (total intended sample size n = 440). Placental biochemical and biophysical cardiovascular markers will be assessed in the first and third trimesters of pregnancy, along with maternal echocardiographic parameters. Fetal cardiac function at third trimester of pregnancy will be also evaluated and correlated with maternal variables. Maternal cardiac function assessment will be determined 12 months after delivery, and correlation with CV and PE risk variables obtained during pregnancy will be evaluated. Discussion The study will contribute to characterize the relationship between anti-angiogenic environment and maternal CV dysfunction/remodeling, during and after pregnancy, as well as its impact on future CVD risk in patients with PE. The ultimate goal is to improve CV health of women with high-risk or previous PE, and thus, reduce the burden of the disease. Trial registration NCT04162236